2012
DOI: 10.4236/jwarp.2012.45031
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Groundwater Suitability for Domestic and Irrigational Purposes: A Case Study from Mingoa River Basin, Yaounde, Cameroon

Abstract: A baseline study involving analyses of subsurface water samples from the Mingoa river basin (longitude: 11°30′E; latitude: 3°52′N) in migmatitic complex in Yaounde Cameroon (central Africa) was carried out to assess their suitability for drinking, domestic and agricultural purposes. Study results show that pH is ranged between 5.1≤ pH ≤ 5.8 and then, induces acidic waters. Groundwater samples are generally characterized by low conductivity values, of which 100% are within the range (55 ≤ EC ≤ 1500 µS/cm). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Results also demonstrated that there is strong correlation between Cl -,Ca 2+ ,Mg 2+ ,SO 2-4..it might be due to similar source like parent material. Similar results were also obtained by other researchers (Ghislain et al, 2012). Results of correlation showed that physicochemical parameters are important in effecting the quality of water i.e.…”
Section: Correlation Matrix (Pearsons)supporting
confidence: 88%
“…Results also demonstrated that there is strong correlation between Cl -,Ca 2+ ,Mg 2+ ,SO 2-4..it might be due to similar source like parent material. Similar results were also obtained by other researchers (Ghislain et al, 2012). Results of correlation showed that physicochemical parameters are important in effecting the quality of water i.e.…”
Section: Correlation Matrix (Pearsons)supporting
confidence: 88%
“…Although a comprehensive hydrogeological investigation has not been made heretofore of the whole city of Yaoundé, many researchers have carried out works on selected groundwater topics and in parts of Yaoundé. Notable amongst them are: Flow dynamics of lineaments in Yaoundé (Teikeu et al, 2016); mass balance of Nitrogen and Potassium in parts of Yaoundé (Kringel et al, 2016); assessment of groundwater quality for domestic and irrigation purposes in parts of Yaoundé (Tabue et al, 2012); use of geoelectric tools to explore the lithostratigraphy of the aquiferous formations in parts of Yaoundé (Teikeu et al, 2012); assessment of bacterial contamination in the Mfoundi Watershed (Kuitcha et al, 2010) and modeling of groundwater flow in Yaoundé IV district (Fouepe et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The bicarbonate was the most abundant in the river water, despite the absence of a dominant carbonate lithology in the study area. The HCO 3 − could be derived from weathering of silicates rocks and CO 2 from soil and organic material [58] [59]. In this study, alkalinity is mainly in the form of bicarbonates.…”
Section: Gibbs Modelmentioning
confidence: 99%